A system study on Montano Foods Corporation - Jose, Brian Christian F. (Animo Repository, 2022)
Montano Foods Corporation is a manufacturer of Bottled Spanish Sardines located in Turno, Dipolog City, Zamboanga Del Norte, Philippines. The processing plant mainly produces six variants of bottled sardines (Corn oil, Olive Oil, Tomato Sauce in Corn Oil, Tomato Sauce in Olive Oil, Tuyo, and Bangus) of Bottled Spanish Style Sardines and supplies to leading stores nationwide. The main problem that was determined, with the help of the WOT-SUG Analysis, in the current production system of the company was the presence of bottled sardine rejects. To be more specific, out of the 965,952 bottles of sardines produced from April 2020 to September 2021, 1170 bottles were considered as rejects which resulted in Php 131,040 in opportunity loss of revenue. Once the presence of bottled sardine rejects was determined to be the main problem of the company, a problem analysis was performed through the construction of a Why-Why diagram. After the initial Why-Why diagram was constructed, the initial causes were then validated. After validating comprehensively, the following were determined to be the actual causes of the presence of bottled sardine rejects: Approximating oil placement (Specific cause of bottled reject caused: Bottle reject due to Oil Shortage and Oil Spillage) Bottles are slid across the table (Specific cause of bottled reject caused: Bottle reject due to Oil Shortage) Workers not fully closing the bottles (Specific cause of bottled reject caused: Bottle reject due to Loose Cap) Deformed bottle cap thread (Specific cause of bottled reject caused: Bottle reject due to Loose Cap) The alternative solutions that were generated revolved around the Oil-Filling step of the production process specifically addressing the validated root causes mentioned above. In choosing the solution to be applied in the proposed system, the KTDA or Kepner-Tregoe Decision Analysis was performed. The criteria taken into consideration for the KTDA were consulted with the management and workers of the company assigned in the oil filling stage. The “Modify Workplace Setup and Equipment Used by the Primary and Secondary Oil Fillers” ended up having the highest rating in the KTDA performed and thus, was the focus of the proposed system. As previously mentioned, the proposed system focused on modifying the workplace setup and equipment used by the Primary and Secondary Oil Fillers. To be more specific, two workers from the preceding stages of the oil filling stage were transferred to the primary oil filling step of the oil filling stage due to the fact that queueing time is incurred before this stage. As a result, there’ll be four primary oil filling workers in the proposed system which is two more compared to the present system. In terms of the equipment, the kettles used by the primary oil fillers and the scoopers with a short handle used by the secondary oil fillers would be replaced by insulated barrels/dispensers with a PVC Transparent hose attached to it. In utilizing this alternative equipment, the proposed system aims to reduce the body pain experienced by workers since the kettles used for oil-filling in the present system contribute to the stress experienced by the workers in parts of their body such as the arms. To have an idea of what implementing the proposed system may look like, a simulation and a cost-benefit analysis were performed. In performing the simulation, it was determined that the proposed system can potentially contribute to the workers being able to fill more sets (1 set = 408 bottles/17 cases) of bottled sardines with oil while incurring lesser overtime compared to the present system. Meanwhile, with the help of the Cost-Benefit Analysis performed, it was estimated that the company can experience an NPV of Php 303,108.